A PSO-CVX Algorithm of Sum and Difference Beam Patterns for Time-Modulated Antenna Array - Xikuan Dong; Hailin Li; Jing Tan; Jiawen Hu; Yachao Jiang (International Journal of Antennas and Propagation)
An integrated optimization of sum and difference beam for time-modulated linear antenna array is studied in this paper. The goal of sum and difference beam synthesis is to generate sum beam in the main band and difference beams in the first-order sideband with low side-lobe level through timing switches. The turn-on times of antenna array are achieved by solving a quadratic constraint linear programming; meanwhile, the opening times are optimized by particle swarm optimization algorithm. The results of linear array show that the sum and difference beam can be scanned within ±40 degrees, with lower peak side-lobe level.